Impact of farmers' associations on household income: Evidence from tea farms in Vietnam - Hung Van Vu; Huong Ho; Le Quoc Hoi (Economies, 2020)
Farmers' associations play an important role to help members increase their access to supports of information, capital, and technology; bring benefits to members; and partly promote production, enhance productivity, and increase income. This paper systematizes the theoretical foundation and empirical evidence on income difference between the member and non-member farmers and identifies factors that affect their decisions to join associations. By comparing specific characteristics between the member and non-member farmers, the paper examines the impact of joining farmers' associations on the income of tea farmers in Vietnam by using the data from the survey of 742 farms. In our sample, 376 respondents are members and 366 non-members of associations in the four largest tea-producing areas, which cover 30 provinces in Vietnam. The paper uses OLS regression model to identify the factors that influence the decision of tea farms to join farmers' organizations and tobit model to assess more detailed impacts of membership on income. The findings show that the farmers, who are members of an association, are more helpful in the ability to access better market services and more tea prices, and are more likely to earn a higher average income than those are non-members. Moreover, their memberships result in an increase of 0.166 unit of income. The research results also show that other factors, including labor, tea price, share of tea sold, farmer age, tea area, ability to access extension services, and credit services, affect the farmer's income.
Keywords: D13; H31; J51; 330; membership; OLS; tobit; Vietnamese Tea Association (VITAS)